Traditional knowledge on ethnobotanical uses of plant biodiversity: a detailed study from the Indian western Himalaya - Singh, Koushalya Nandan (Biodiversity: Research and Conservation, 2013)
The present article is based on the findings of ethnobotanical surveys conducted in the entire Lahaul-Spiti region of Indian western Himalaya to highlight the traditional use of medicinal plants by the native people. Results revealed that tribal communities of both Lahaul and Spiti valleys (Lahaulas in Lahaul and Bhotias in Spiti) have a great respect for and faith in Amchi system of medicine practiced in the entire region. Information collected on the traditional use of plants in the local health care system by the tribal communities of Lahaul-Spiti revealed the use of 86 plant species belonging to 69 genera and 34 families to cure about 70 different ailments. Maximum number of plant species used in herbal formulations belonged to families Asteraceae, Apiaceae, Gentianaceae, and Polygonaceae. Both single herbal preparations and polyherbal formulations are prescribed and administered by local healers known as Larje in Lahaul and Amchis in Spiti. Most of the medicines are prescribed in a powder form, some as juice and decoctions. Among plant parts, leaves were recorded to be used to a large extent as a remedy, followed by flowers. Results of the present study show that the highest number of plants was used to cure stomach disorders, while the highest extent of phytotherapeutic use among all the species had Hippophae rhamnoides (17.14%). The obtained data also revealed the information on new or less known medicinal uses of various plant species that are new addition to the traditional knowledge from western Himalaya. Modes of preparation, administration and dosage are discussed along with the family and local names of plants and plant parts used.